Poor Education, Unemployment and National Security in Nigeria - Tukur, Ibrahim Talasse; Aguiyi, Chukwuebuka Cornelius (NIU Journal of Social Sciences, 2022)
The study examined poor education and unemployment as threat for national security in Nigeria with the objectives to establish the relationship between poor education, unemployment and national security; trace the historical antecedents of education and unemployment in Nigeria; examine the causes of poor education and unemployment in Nigeria; examine the challenges of poor education and unemployment for Nigeriaâ€™s national security; and proffer ways of improving education to generate employment for enhanced national security. Data for the study were sourced from both primary and secondary sources. Primary data were collected through questionnaires administered to 100 respondents of which 94 were returned. The secondary data were gotten from both published and unpublished materials. From the responses to the questionnaire, 82.2 respondents affirmed the finding of this study. The study found that poor education and unemployment have social, economic and political effects on national security these are in the areas of health, education, social protection to mention but few. It also established that the challenges of poor education and unemployment for national security are that of high crime rate, increase civil unrest, increase cyber-crime and undermines economic security.  The study concluded that poor education and unemployment are threat to national security. Based on its findings, the study however recommended that: the Federal Government of Nigeria should set up Agricultural Development Youth Fund (AYDF) that will be saddled with the responsibility of investing massively in agriculture and also encourage youths into it. The Federal Ministry of Education should set up a body that will be charged with the responsibility of total overhauling of the curriculum at all levels of education. The governments at both federal and state levels should set up a joint body that will be saddle with the responsibility of checking rural urban migration through the provision of essential social amenities that will make life in the rural areas attractive to the youths. Then Federal government of Nigeria should provide more funding for the educational sector. Keywords: National Security, Education, Unemployment, Curriculum, Anambra State.